1995
DOI: 10.1002/ijc.2910600318
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies against linear and conformational epitopes of human papillomavirus type 16 that independently associate with incident cervical cancer

Abstract: In a seroepidemiological study of incident cervical cancer, 94 cases and I88 population-based controls were used to evaluate the disease-association of IgG and IgA antibody responses against 6 human papillomavirus (HPV) type-I 6 antigens. Nine of the tested antibody responses were positively associated with cervical cancer, with odds ratios (ORs) ranging from 2.5 to 15.0.The antibody responses most strongly associated with cervical cancer were IgA against E6:IO, an epitope derived from the carboxyterminal part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…Some of the previous studies found considerable variation in the association between HPV 16 exposure and the risk of ESCC when they changed their cutpoints. 9,10 For example, in Bjorge's study 9 the OR for the association of HPV 16 and ESCC changed from 10 for a cutpoint of 0.239 (a level that that had given optimal discrimination of cases and controls in a previous study 27 ) to 2.3 for a cutpoint of 0.100 (a level that distinguishes HPV 16 infected women from sexually inexperienced women 28 ). To overcome this problem, we examined graphs of risk versus type-specific log OD produced by cubic spline logistic regressions and defined a spline cutpoint as the inflection point beyond which the graph either monotonically increased or decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the previous studies found considerable variation in the association between HPV 16 exposure and the risk of ESCC when they changed their cutpoints. 9,10 For example, in Bjorge's study 9 the OR for the association of HPV 16 and ESCC changed from 10 for a cutpoint of 0.239 (a level that that had given optimal discrimination of cases and controls in a previous study 27 ) to 2.3 for a cutpoint of 0.100 (a level that distinguishes HPV 16 infected women from sexually inexperienced women 28 ). To overcome this problem, we examined graphs of risk versus type-specific log OD produced by cubic spline logistic regressions and defined a spline cutpoint as the inflection point beyond which the graph either monotonically increased or decreased.…”
Section: Discussionmentioning
confidence: 99%
“…HPV seropositivity was determined by the standard ELISA assay using baculovirus-expressed capsids (23) with disrupted capsids of bovine papillomavirus as negative control (24,25). The HPV-16 capsids were obtained from Dr. John T. Schiller (National Cancer Institute, Bethesda, MD) and the HPV-18 and HPV-33 capsids were obtained from Dr. Martin Sapp (University of Mainz, Mainz, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Patients with cervical cancer and normal subjects were, however, more clearly distinguished using a higher cutoff level (which, relative to internal standards, corresponds to 0.277 absorbance unit in the present study; ref. 24) presumably because rapidly cleared (transient) infections induced lower levels of antibodies than do persistent infections (27). For the other HPV types, comparable alternatives of cutoff levels for HPV-18 (low, 0.100; high, 0.200) and HPV-33 (low, 0.113; high, 0.224) absorbance units were used.…”
Section: Methodsmentioning
confidence: 99%
“…Serologic titers can be quantified and related to clinical disease status. 13,15,16 The use of type-specific HPV VLP antibody ELISA assays may identify women with chronic HPV infection. 15,17,18 Since the development of antibodies has been associated with persistent infection, we hypothesized that women with higher-grade CIN lesions will have a higher prevalence of HPV type-specific antibodies than women with low-grade lesions or no CIN.…”
mentioning
confidence: 99%
“…[9][10][11] Antibodies to conformational epitopes on synthetically produced virus-like particles (VLPs), which are similar to the HPV virion, have been shown to develop in response to infection. [12][13][14] Serologic responses directed at type-specific epitopes on VLPs are often detectable when there is clinical evidence of disease. Serologic titers can be quantified and related to clinical disease status.…”
mentioning
confidence: 99%